Intergroup bias in punishing behaviors of adults with autism spectrum disorder - Qian, Chenyu; Tei, Shisei; Itahashi, Takashi; Aoki, Yuta Y.; Ohta, Haruhisa; Hashimoto, Ryu-ichiro; Nakamura, Motoaki; Takahashi, Hidehiko; Kato, Nobumasa; Fujino, Junya (Frontiers in Psychiatry, 2022)
Groups are essential elements of society, humans, by nature, commonly manifest intergroup bias (i.e., behave more positively toward an ingroup member than toward an outgroup member). Despite the growing evidence of various types of altered decision-making in individuals with autism spectrum disorder (ASD), their behavior under the situation involving group membership remains largely unexplored. By modifying a third-party punishment paradigm, we investigated intergroup bias in individuals with ASD and typical development (TD). In our experiment, participants, who were considered as the third-party, observed a dictator game in which proposers could decide how to distribute the money while receivers could only accept unconditionally. Participants were confronted with two different group situations: the proposer was an ingroup member and the recipient was an outgroup member (IN/OUT condition), or the proposer was an outgroup member and the recipient was an ingroup member (OUT/IN condition). Participants with TD punished proposers more severely when violating social norms in the OUT/IN condition than in IN/OUT condition, indicating that their decisions were influenced by the intergroup context. This intergroup bias was attenuated in individuals with ASD. Our findings deepen the understanding of altered decision-making and socioeconomic behaviors in individuals with ASD.